New Discovery of P2P Botnets Attack Pattern within Host-and-Network Atmosphere - Raihana Syahirah Abdullah, Raihana S.A.; Faizal M.A., Faizal M.A.; Zul Azri Muhamad Noh, ZAM Noh (2013)
The attacks of advanced P2P botnets become critical threats to the Internet security. Nowadays, powerful botnets creates to make this botnets stronger and immune from any prevention techniques. Hence, studies of attack pattern required on detecting and restructuring the security of the network that has been attacked. This paper proposes a new generalization of P2P botnets attack pattern that conducted within host and network atmosphere. In each attack steps, the investigation of P2P botnets has been conducted to identify the characteristics and the behaviors. Then, detailed analyses on infected files have been conducted that cover both of host log and network log in different OSI layer via hybrid analyzer. This P2P botnets hybrid analyzer can be abstracted to form P2P botnets attack patterns. In advances, this paper verifies the new discovery attack pattern has achieved new level of accuracy and efficiency. Furthermore, this P2P botnets attack pattern will beneficial to the P2P botnets detection and computer forensic investigation.